Cálculo diferencial no ensino médio: uma abordagem possível e interdisciplinar com auxílio da tecnologia - Petry, Morgana (Universidade do Vale do Rio dos Sinos, 2016)
This paper aims to analyze the possibility of teaching intuitive notions of Differential Calculus in High School by studying the rate of change of a function, particularly in its intertwining with Physics and with the use of GeoGebra software. In a workshop carried out with 10 High School students attending a state school in Estância Velha (RS), activities were developed by means of four didactic sequences and performed in four in person meetings. The first three didactic sequences supported the topics of related function, quadratic function and limits of functions, respectively, and grounded the study of derivative, the central focus of both the last meeting and this paper. The qualitative study, triggered by experimentation with documental research, evidenced that it is possible to introduce notions of derivative in Basic Education, but without emphasizing more specific and formal nomenclatures addressed in Higher Education. Therefore, if interpreted in a more dynamic, visual and experimental way, as instantaneous rate of change and inclination of tangente straight line, and in accordance with the education level, Differential Calculus can enable High School students to have a meaningful contact with such important concepts in Mathematics.
Keywords: Cálculo diferencial; Ensino médio; Interdisciplinaridade; Differential calculus; High school; GeoGebra; Interdisciplinarity